1986
DOI: 10.1538/expanim1978.35.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Growth Experiment of Hantaan Virus in A549 Cells: An Attempt to Improve the Immunofluorescent Antibody Technique for Hemorrhagic Fever with Renal Syndrome

Abstract: An assay method for the infectivity of Hantaan virus, a causative agent of HFRS (hemorrhagic fever with renal syndrome), was developed by the use of IFA (immunofluorescent antibody technique).With the aid of this method, the growth characteristics of Hantaan virus, 76-118 strain, were followed in A549 cells . At a maximal MOI (multiplicity of infection) of 1.6 VAIU (viral antigen inducing units) per cell, the conventionally available value, plateau level potencies of the viral antigen and virus infectivity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Since it has been proposed that macrophages may contribute to the spread of Hantaan virus, possibly through an antibody-dependent enhancement (ADE) (Yao et al, 1992), it is of interest that macrophages also support Puumala virus replication. Susceptibility of the lung-, submaxillary gland-and pharynx-derived cells (CCD-I 1 Lu, A-427, WI-38, A-253, Detroit 562) is in line with the reported sensitivity of A-549 cells (human lung carcinoma) to Hantaan virus (Hamada et al, 1986) and the proposed entry of hantaviruses through the respiratory tract. Susceptibility of the Hep G2 hepatoblastoma line suggests that the involvement of liver with elevated transaminases in NE (Lfihdevirta et al, 1984;Settergren et al, 1989) could be a consequence of virus propagation in this organ.…”
supporting
confidence: 64%
“…Since it has been proposed that macrophages may contribute to the spread of Hantaan virus, possibly through an antibody-dependent enhancement (ADE) (Yao et al, 1992), it is of interest that macrophages also support Puumala virus replication. Susceptibility of the lung-, submaxillary gland-and pharynx-derived cells (CCD-I 1 Lu, A-427, WI-38, A-253, Detroit 562) is in line with the reported sensitivity of A-549 cells (human lung carcinoma) to Hantaan virus (Hamada et al, 1986) and the proposed entry of hantaviruses through the respiratory tract. Susceptibility of the Hep G2 hepatoblastoma line suggests that the involvement of liver with elevated transaminases in NE (Lfihdevirta et al, 1984;Settergren et al, 1989) could be a consequence of virus propagation in this organ.…”
supporting
confidence: 64%
“…EVC-304 cells are also endovascular cells, whereas EVC-304 TLR4 − cells are TLR4-deleted cells, both of which have been used for HTNV infection related studies (15, 33). A549 cells were once used to isolate HTNV, and they were confirmed to be a mature model of infection (3437). Additionally, Huh 7.0 and Huh 7.5 (RIG-I − ) cells used in our study have been reported to be infected by HTNV by Lee et al (5) and can be used as a cell model to study immune responses against HTNV replication (38, 39).…”
Section: Discussionmentioning
confidence: 99%